Evolution of physical and photocatalytic properties of new Zn(II) and Ru(II) complexes. (15th September 2019) - Gugulothu, Venkanna; Ahemed, Jakeer; Subburu, Mahesh; Yadagiri, Bhongiri; Mittal, Ritu; Prabhakar, Chetti; Pola, Someshwar
Graphical abstract: Synthesis and characterization of new [Zn(TPTTP)]Cl2 and Ru(TPTTP)Cl2 and their photocatalytic activity studies through CH bond activation (sp 3 and sp 2 ) under visible light irradiation. Abstract: Synthesis of Zn(II) and Ru(II) complexes were reported by using N4 -macrocyclic Schiff base ligands under solvothermal conditions. The newly synthesized Zn(II) and Ru(II) complexes have been characterized by various physico-chemical techniques such as elemental analysis, molar conductance, HRMS, TGA, FESEM, UV–Vis, FT-IR, 1 H NMR, and cyclic voltammetry. By using molar conductance studies, the complexes are formulated as [Zn(TPTTP)]Cl2 and [Ru(TPTTP)Cl2 ]. CH bond activation of an sp 3 group of methylstyrenes (converted into cinnamaldehydes) and CH bond activation of the sp 2 bond of polycyclic aromatic hydrocarbons through photooxidation was examined in the presence of Zn(II) and Ru(II) complexes. Reusable activity studies and photostability of catalyst are investigated by using UV–Vis spectra. Based on the results, higher catalytic activity of [Ru(TPTTP)Cl2 ] complex than [Zn(TPTTP)]Cl2 complex in both CH bond activation and photooxidation of aromatic hydrocarbons has been reported.